2012
DOI: 10.5194/cp-8-1109-2012
|View full text |Cite
|
Sign up to set email alerts
|

Ranges of moisture-source temperature estimated from Antarctic ice cores stable isotope records over glacial–interglacial cycles

Abstract: Abstract.A single isotope ratio (δD or δ 18 O) of water is widely used as an air-temperature proxy in Antarctic ice core records. These isotope ratios, however, do not solely depend on air-temperature but also on the extent of distillation of heavy isotopes out of atmospheric water vapor from an oceanic moisture source to a precipitation site. The temperature changes at the oceanic moisture source ( T source ) and at the precipitation site ( T site ) can be retrieved by using deuterium-excess (d) data. A new d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
189
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 127 publications
(202 citation statements)
references
References 76 publications
11
189
1
1
Order By: Relevance
“…From their study with an idealised model, and using monthly mean data for the initialisation, Johnsen et al (1989) concluded that SST and RH changes could both play a role for d variations observed in a Greenland ice core. Noting that GCM (global circulation model) simulations show only small glacial-to-interglacial changes in mean oceanic RH, it has been proposed that d in Antarctic ice core records can be interpreted as a moisture source SST signal only (Vimeux et al, 1999;Stenni et al, 2001;Uemura et al, 2012), revoking the earlier interpretation as a proxy of moisture source RH (Jouzel et al, 1982). This interpretation as source SST has later been extended also to Greenland ice cores (MassonDelmotte et al, 2005).…”
Section: Introductionmentioning
confidence: 77%
“…From their study with an idealised model, and using monthly mean data for the initialisation, Johnsen et al (1989) concluded that SST and RH changes could both play a role for d variations observed in a Greenland ice core. Noting that GCM (global circulation model) simulations show only small glacial-to-interglacial changes in mean oceanic RH, it has been proposed that d in Antarctic ice core records can be interpreted as a moisture source SST signal only (Vimeux et al, 1999;Stenni et al, 2001;Uemura et al, 2012), revoking the earlier interpretation as a proxy of moisture source RH (Jouzel et al, 1982). This interpretation as source SST has later been extended also to Greenland ice cores (MassonDelmotte et al, 2005).…”
Section: Introductionmentioning
confidence: 77%
“…This link has further been confirmed for polar snow Petit et al, 1991;Ciais and Jouzel, 1994); its use for extracting information about moisture sources was developed in the eighties (Jouzel et al, 1982;White et al, 1988;Dansgaard et al, 1989;Johnsen et al, 1989). Since then, δD and δ 18 O are quite systematically measured in order to provide such additional information from ice cores drilled in both Antarctica (Jouzel et al, 1982;Vimeux et al, 1999Vimeux et al, , 2002Cuffey and Vimeux, 2001;Stenni et al, 2001Stenni et al, , 2003Stenni et al, , 2010Uemura et al, 2004Uemura et al, , 2012 and Greenland (Masson- Jouzel et al, 2007b), where deuterium excess is also used as a marker of rapid climatic changes .…”
Section: Combining Information From δD δ 18 O and δ 17 Omentioning
confidence: 86%
“…The present-day conditions at these three dry and particularly cold sites depict differences in the distance to open ocean, elevation (within 577 m), albedo (within 3 %), wind speed (a factor of two), accumulation (within 15 %) and mean annual temperature (within 2.5 • C) ( Table 1). MIS 5 is characterized by large precession parameter variations, together with large glacial-interglacial changes in Antarctic temperature, and is featured with warmer-than-present reconstructed interglacial temperatures (Sime et al, 2009;Stenni et al, 2010;Masson-Delmotte et al, 2011;Uemura et al, 2012). Figure 3 displays the δO 2 /N 2 records from Dome F (transferred on AICC2012 using volcanic matching (Appendix B), Fujita et al, 2015;Kawamura et al, 2007), EDC and Vostok (both on their respective AICC2012 chronologies, Veres et al, 2013;Bazin et al, 2013) from 100 to 150 ka.…”
Section: Mis 5 Antarctic Inter-comparisonmentioning
confidence: 99%